A new method for determining strength parameters of rock using digital drilling technology - Qiang, Guo; Ma, Xudong; Liu, Xinxing (Frontiers in Earth Science, 2023)
Fast and accurate prediction for mechanical parameters of rock mass is an important prerequisite for guiding the safe construction of rock engineering. At present, the rock strength parameters test requires well-prepared samples; sample preparation is time consuming, costly, and difficult as well as destructive, in particular the polishing and rectification of the sample ends. In this paper, the mathematical model of the drilling process is established based on the force characteristics of the drill bit and the principle of mechanical limit equilibrium. The digital drilling tests are carried out on four types of rocks to drilling characteristics using the digital drilling system. The concept of cutting strength ratio is proposed to analyze the correlation between cutting strength ratio and rock internal friction angle and cohesion. A new method is proposed for determining the compressive and tensile strength of rock. The results show that the cutting strength ratio increases with the increasing of internal friction angle and cohesion. The uniaxial compressive strength and tensile strength of rock increase linearly with the cutting strength ratio. The average error of rock tensile strength is 12.29%, and the average error of uniaxial compressive strength is 20.44%. The internal friction angle of rock obtained based on the digital drilling technology is consistent with the value measured by the laboratory standard test. This method can provide a new way to determine rock strength parameters in real time.